2015
DOI: 10.1186/s13017-015-0003-z
|View full text |Cite|
|
Sign up to set email alerts
|

Poor prognostic factors in patients who underwent surgery for acute non-occlusive ischemic colitis

Abstract: IntroductionIschemic colitis (IC) is a disease with high postoperative morbidity and mortality. Knowledge of the risk factors for postoperative mortality could be helpful in clinical decision making and in optimizing postoperative treatment.MethodsFrom a prospective database, we conducted a retrospective medical record review of 50 patients who underwent surgery for IC between 2003 and 2011 at our institution. We analyzed the causes and potential risk factors for early mortality after surgery for IC.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…In a small subgroup of patients presenting with severe colitis, however, emergency colectomy is usually for nonresponsiveness to medical treatment [10], severe ischaemic colitis [11], intestinal perforation or massive colonic distension [12,13]. At the present time the results of surgical resection in patients presenting with neuroleptic-induced colitis have only been reported in small series [2,5,7,14] with rates of morbidity and mortality of 50% and 30% [2,[14][15][16]. The long-term outcome including after restoration of intestinal continuity and the incidence of a definitive stoma has not been evaluated [17].…”
Section: Resultsmentioning
confidence: 99%
“…In a small subgroup of patients presenting with severe colitis, however, emergency colectomy is usually for nonresponsiveness to medical treatment [10], severe ischaemic colitis [11], intestinal perforation or massive colonic distension [12,13]. At the present time the results of surgical resection in patients presenting with neuroleptic-induced colitis have only been reported in small series [2,5,7,14] with rates of morbidity and mortality of 50% and 30% [2,[14][15][16]. The long-term outcome including after restoration of intestinal continuity and the incidence of a definitive stoma has not been evaluated [17].…”
Section: Resultsmentioning
confidence: 99%
“…This finding has rarely been studied in published literature; in a retrospective study of 50 patients, Noh et al demonstrated a 73.3% mortality rate vs 34.3% mortality rate when surgery was delayed for >3 days. 10 Unfortunately, due to the inherent limitations of the database, we cannot tell if this is a delay in diagnosis, surgical consultation or surgical intervention. Regardless, this finding highlights the importance of early diagnosis for ischemic colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Noh et al ( 21 ) from Korea, in a retrospective study involving 50 patients who were treated surgically for IC, found that 78% of patients had co morbid conditions, such as cancer, hypertension, coronary artery disease, diabetes mellitus, nephropathy, previous abdominal or vascular surgery, respiratory disease, and liver cirrhosis. Hypertension was the most common co morbid condition (46%), followed by diabetes mellitus, nephropathy, and coronary artery disease.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Noh et al performed a retrospective analysis of 50 patients who were operated on for acute non-occlusive IC ( 21 ). They found that postoperative mortality was associated with coronary artery disease, preoperative nephropathy, previous history of cardiovascular surgery, ASA score ≥4, surgical delay ≥3 days, preoperative hemodynamic instability, and use of adrenergic vasopressors.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%